Pertanggungjawaban Pidana Korporasi dalam Tindak Pidana Pendanaan Terorisme Ditinjau dari Hukum Pidana dan Hukum Pidana Islam: Criminal Liability of Corporations in Terrorism Financing Crimes Reviewed from Criminal Law and Islamic Criminal Law - Muhammad RIzky Afwan Fanani (CLEAR: Criminal Law Review, 2023)
The main focus of this research is: 1) What is the form of corporate criminal liability in the crime of financing terrorism? 2) What is the form of corporate criminal liability in the criminal act of financing terrorism in terms of Islamic Criminal Law? In research methods, it uses normative juridical research with statutory, conceptual and comparative approaches which are relevant to the title of this research. The analysis technique uses literature study. In this research, 2 conclusions can be drawn, namely: 1) The form of corporate criminal responsibility for the crime of financing terrorism refers to Law Number 9 of 2013 concerning the Prevention and Eradication of Criminal Acts of Terrorism Funding. Corporations are subject to a basic criminal charge, namely a fine of up to Rp. 100,000,000,000 (one hundred billion rupiah). 2) The form of corporate criminal responsibility for acts of terrorist financing when viewed from Islamic criminal law is Ta'zir. Ta'zir punishment is given only to administrators or those in charge. This is because themukallaf, which is one of the conditions for criminal responsibility, is only owned by humans, because a corporation explicitly does not have the mind, let alone the will to do something, so it cannot be charged with legal responsibility.. Fokus utama dalam penelitian ini adalah: 1) Apakah bentuk Pertanggungjawaban pidana korporasi dalam tindak pidana pendanaan terorisme? 2) Bagaimana bentuk pertanggungjawaban pidana korporasi dalam tindak pidana pendanaan terorisme ditinjau dari Hukum Pidana Islam? Dalam metode penelitian, menggunakan jenis penelitian yuridis normatif dengan pendekatan perundang-undangan, konseptual dan perbandingan yang mempunyai relevansi dengan judul penelitian ini. Teknik analisisnya menggunakan studi kepustakaan. Dalam Penelitian ini, dapat disimpulkan 2 kesimpulan yaitu: 1) Bentuk pertanggungjawaban pidana korporasi dalam tindak pidana pendanaan terorisme merujuk pada Undang-Undang Nomor 9 Tahun 2013 Tentang Pencegahan dan Pemberantasan Tindak pidana Pendanaan Terorisme. Korporasi dibebani pidana pokok yaitu denda paling banyak Rp. 100.000.000.000 (seratus miliar rupiah). 2) Bentuk pertanggungjawaban pidana korporasi dalam tindak pendanaan terorisme jika ditinjau dari hukum pidana Islam adalah Ta’zir. Hukuman Ta’zir diberikan hanya kepada pengurus atau yang bertanggung jawab saja. hal ini disebabkan karena mukallaf yang menjadi salah satu syarat pertanggungjawaban pidana hanyalah dimiliki oleh manusia saja, karena sebuah korporasi secara eskplisit tidak memiliki akal apalagi kehendak dalam berbuat sesuatu hingga tidak dapat dibebankan pertanggungjawaban hukum